Highly Sensitive, Non-cryogenic NIR High-resolution Spectrograph, WINERED. (11th January 2022) - Ikeda, Yuji; Kondo, Sohei; Otsubo, Shogo; Hamano, Satoshi; Yasui, Chikako; Matsunaga, Noriyuki; Sameshima, Hiroaki; Yoshikawa, Tomohiro; Fukue, Kei; Nakanishi, Kenshi; Kawanishi, Takafumi; Watase, Ayaka; et al.
Abstract: WINERED is a novel near-infrared (NIR) high-resolution spectrograph (HRS) that pursues the highest possible sensitivity to realize high-precision spectroscopy in the NIR as in the optical wavelength range. WINERED covers 0.9–1.35 μ m ( z, Y, and J -bands) with three modes (Wide mode and two Hires modes) at the maximum spectral resolutions of R = 28, 000 and R = 70, 000. For fulfilling the objective, WINERED is designed with an unprecedentedly high instrument throughput (up to 50% at maximum including the quantum efficiency of the array) that is three times or more than other existing optical/NIR HRSs. This is mainly realized by a combination of non-white pupil and no fiber-fed configuration in optical design, the moderate (optimized) wavelength coverage, and the high-throughput gratings. Another prominent feature of WINERED is "warm" instrument despite for infrared (IR) observations. Such non-cryogenic (no cold stop) IR instrument finally became possible with the combination of custom-made thermal-cut filter of 10 −8 class, 1.7 μ m cutoff HAWAII-2RG array, and a cold baffle reducing the direct thermal radiation to the IR array into the solid angle of f /2. The thermal background is suppressed below 0.1 photons pixel −1 s −1 even in the wide band of 0.9–1.35 μ m under the environment of 290 K. WINERED had been installed to the 3.58 m New Technology Telescope at La Silla Observatory, ESO, since 2017. Even with the intermediate size telescope, WINERED was confirmed to provide a limiting magnitude (for SNR = 30 with 8 hr. integration time) of J = 16.4 mag for the Wide mode and J = 15.1 mag for the Hires mode, respectively, under the natural seeing conditions. These sensitivities are comparable to those for the existing NIR-HRSs attached to the 8–10 m class telescopes with AO. WINERED type spectrographs may become a critical not only for the currently on-going extremely large telescopes to reduce the developing cost and time but also for smaller telescopes to extend their lives with long programs.